Regulating Generative AI Technologies and Their Impact on Futuristic Research and Innovation - Bapat, Bhalchandra (Digital Repository of Theses, 2024)
This study investigates the regulatory landscape surrounding generative AI (GenAI) technologies and their implications for research and innovation in India. The objectives are to identify crucial regulatory aspects for GenAI, analyse privacy concerns and power dynamics impacting its adoption, evaluate the influence of existing government policies and legislation, assess the effectiveness of Indian regulatory bodies, and recommend a robust regulatory framework. The research addresses five key questions: the essential elements of GenAI regulations, the influence of privacy and power dynamics on GenAI implementation, the impact of current policies on regulatory effectiveness, the role of regulatory bodies in technology adoption, and the effect of regulations on futuristic research and innovation. The study employs a comprehensive analysis of existing regulations and frameworks, privacy concerns, and the role of Indian regulatory bodies in shaping the technologies of GenAI. Overall, 480 relevant stakeholders were enrolled in the study. It examines the effectiveness of government policies and legislation in addressing the unique challenges posed by GenAI. The research finds that significant differences exist in the regulatory aspects of GenAI, particularly concerning considerations, security standards, accountability, transparency, and explain ability. Additionally, the impact of current policies and legislation on regulatory effectiveness is substantial, highlighting areas for improvement. The study also reveals that Indian regulatory bodies play a critical role in shaping GenAI adoption, though there is room for enhancement in their strategies. The findings underscore the need for a well-defined regulatory framework to address privacy concerns and power dynamics, ensuring that GenAI technologies can be effectively regulated while fostering innovation. Recommendations include refining existing regulations and developing new guidelines to balance regulatory oversight with technological advancement. This study provides valuable insights into the regulatory challenges and opportunities associated with GenAI, contributing to the formulation of policies that support both technological progress and ethical considerations.